Understanding the effects of local and landscape variables on vegetable farm arthropod communities - Schieuer, Kaitlin Grace (My University, 2026)
Urbanization is one of the main contributing factors to insect declines globally. To mitigate the losses of arthropods and other organisms, urban green spaces have been incorporated into city landscapes. Urban agriculture (UA) is a form of green space that has gained significant attention in the last decade. UA includes community gardens, vegetable farms, green roofs, home gardens, and many other similar land uses. This type of green space has been promoted as a beneficial habitat for arthropods. However, it is unclear how local and landscape variation across farms and gardens affects these green spaces’ capacity to harbor diverse arthropods. Comparisons of habitat efficacy are also lacking between farms and other forms of green space, especially natural areas. Few studies examine the arthropod community broadly and encompass a range of feeding guilds and foraging strata. We addressed these knowledge gaps by examining the effects of landscape (developed cover) and local variables (plant richness, farm size, and habitat type) on arthropod groups (ground herbivores, foliar herbivores, ground predators, foliar predators, and pollinators) at vegetable farms practicing organic growing techniques and restored prairies in two field studies. The objectives of this project were to evaluate how local and landscape variables affect (A) the abundance and community composition of various arthropod guilds and (B) the community stability and foraging behavior of pollinators. Our first study found that local variables were more influential than landscape variables in shaping the abundance and composition of ground herbivores, foliar herbivores, and foliar predators. However, we did find that in some cases abundance and composition were affected by interactions between local and landscape variables. Specifically, developed cover mediated the effects of crop richness on the abundance and composition of pollinators and the composition of foliar herbivores. Additionally, farms and prairies supported similar types and quantities of pollinators and similar quantities of ground-dwelling predators. We also found that urban and peri-urban farms supported significantly more foliar predators than prairies. These findings support the claim that vegetable farms are favorable habitats for beneficial arthropods. Our second study examined the pollinator community more closely and used a plant-pollinator network approach to investigate community stability and foraging behavior. Pollinator species composition differed across urban and rural farms as well as between rural farms and prairies. However, no significant differences in community stability (network modularity) or foraging behavior (network specialization) were observed. Depending on conservation goals, prairies and some vegetable farms may be interchangeable habitats for pollinators. For example, if the purpose is to restore ecosystem function (i.e., stability, plant visitation patterns) to a landscape, these habitats may be equivalent. However, if the goal is to provide habitat for certain rare pollinators, these habitats may not have the same value. These two studies showed that farms, and specifically UA, can be a beneficial habitat for arthropods of various feeding guilds. Farms may also support similar or greater quantities and types of certain arthropods compared to prairies. Incorporating more UA as green spaces in cities may help reduce local arthropod declines, as these spaces do harbor beneficial insects. As urbanization continues to change the landscape globally, retaining green spaces like UA will be important for promoting and maintaining ecological diversity.
Keywords: Entomology; Urban agriculture